The Impact of BMI on Self-Concept in Adolescents with Pubertal Gynecomastia - Nazan Kaymaz; Özlem Kara; Tolga Kasap; Mehmet Erdem Uzun; Hande Şirin (Güncel Pediatri)
Introduction: Physiological changes in the body may result in anxiety and impaired self-concept during adolescence. Although temporary, pubertal gynecomastia (PG) may cause negative emotions that interrupt the development of self-concept by causing a physical appearance that does not fit the male gender. This paper aimed to identify whether the self-concept level of adolescents with PG is moderated by their anthropometrics. Materials and Methods: This case-control study included adolescent males, with pubertal stage assessed using the Marshall and Tanner criteria. PG was diagnosed by palpation of a subareolar glandular disc. Anthropometric measurements were obtained by trained pediatric endocrinology clinic staff, and self-concept was evaluated using the Piers-Harris Children’s Self-Concept Scale (PHCSCS). To specify relationships correlation and regression analysis were examined. Results: The study included 38 adolescents with PG and 61 age- and pubertal stage-matched controls. BMI was significantly higher in the PG group, and self-concept scores declined with increasing BMI (p=0.044; r=-0.437, p=0.006). PG subjects at Tanner Stage 3 were shorter than controls (p=0.03) and had lower happiness and behavior subscale scores (p=0.01; p=0.04). PG duration was negatively correlated with total self-concept (r=-0.400, p=0.013) and the subscales of happiness (r=-0.456), behavior (r=-0.334), and physical appearance (r=-0.354). Conclusion: Adolescents with PG demonstrated lower self-concept, particularly in relation to higher BMI, shorter stature at mid-puberty, and prolonged symptom duration. These findings highlight the need for early psychosocial support in affected individuals.